Analysing Content Coverage of the Listening and Reading Papers of the National Foreign Languages’ Examinations in Lithuania - Juknevičienė, Rita (Kalbotyra, 2006)
The article describes an attempt to analyze content coverage of the Listening and Reading Papers of the national foreign languages’ (English, French, German and Russian) examinations in Lithuania. The research project was specifically focused on the test papers of the main examination sessions administered in the country in 2002–2005 and the examination syllabus. The results of the analysis reveal certain tendencies in the selection and exploitation of topics included in the examination syllabus. It is also argued that texts used in the tasks of receptive language skills of the four tested languages have a different proportion and varying density of low frequency lexical items which create the topic of the text and contribute to the test difficulty. It is therefore proposed that a set of explicit criteria for texts used in listening and reading tests of certain level should be developed to ensure consistency of thematic expression.